An overview of palaeomagnetic chronology with special reference to the South African hominid sites - McFadden, P. L. (Bernard Price Institute for Palaeontological Research, 1980)
The phenomena of secular variation, polarity reversals and apparent polar wander are discussed. The calibration of each of these phenomena for use in palaeomagnetic chronology is outlined and the use of each of these calibrated scales for dating is briefly explained. A successful application of the polarity reversal dating technique is presented as an example of the potential for palaeomagnetic chronology in South Africa. In this example it is shown that the age of the important Member 3 in Makapan is about 3 My. It is concluded that palaeomagnetic chronology has a vast potential in South Africa ; a palaeomagnetic laboratory specifically oriented to chronological problems would be extremely valuable.
Main article
Keywords: palaeomagnetic; hominid sites; South Africa